1,3-thiazolium-5-thiolates mesoionic compounds: semiempirical evaluation of their first static hyperpolarizabilities and synthesis of new examples - Lyra,Bruno F. (2010)
Semiempirical AM1-TDHF calculations of the static first hyperpolarizabilities, β(0), of 1,3-thiazolium-5-thiolate mesoionic derivatives were performed. Guided by these results, two new mesoionic compounds - 2-(4-nitrophenyl)-3-methyl-4-(methylphenyl)-1,3-thiazolium-5-thiolate and 2-(4-nitrophenyl)-3-methyl-4-(methoxyphenyl)-1,3-thiazolium-5-thiolate - were synthesized and characterized by analytical and spectroscopic means.